Giustizia religiosa e islam. Il caso degli Shariah Councils nel Regno Unito (Stato, Chiese e pluralismo confessionale, 2016)
Lo scritto, sottoposto a valutazione, rappresenta la versione ampliata e rivista di un intervento intitolato ‘Gli Sharīʿah Councils nel Regno Unito’ presentato il 3 maggio 2016 all’Università degli Studi di Torino, quale parte del ciclo di incontri “Le relazioni familiari nel diritto interculturale, Il ruolo del giudice nell’adattamento interculturale del diritto familiare, tribunali statali e tribunali religiosi a confronto”; lo scritto è destinato alla pubblicazione degli atti del ciclo di incontri “Le relazioni familiari nel diritto interculturale. Diritto interculturale tra ordinamenti statali e religioni”, nel volume Relazioni familiari nel diritto interculturale, a cura di I. Zuanazzi, Tricase, Libellula University Press, 2017SOMMARIO: 1. Introduzione - 2. La cornice del dibattito - 3. L’indagine ministeriale - 4. Il quadro descrittivo delle attività di ricerca - 5. Le difficoltà dell’indagine empirica - 6. Gruppi tematici e problematiche di ricerca - 7. Aspetti fondamentali ed elementi chiave - 8. Proposte di legge - 9. Riflessioni conclusive sulla giustizia religiosa sciaraitica.Faith-based justice and Islām. Sharīʿah Councils in the UKABSTRACT: In 2008, a vivid debate was stirred by the lecture delivered in the Royal Courts of Justice by the then Archbishop of Canterbury. Public discussion and social commentary began to question the role that sharīʿah was playing in the British society and the Sharīʿah Councils were immediately identified as proponents of a "parallel" legal system. Whilst media coverage was causing much anxiety, the narrative on "inherently discriminatory" legal orders operating in the shadow of state law exponentially grew.This social critique soon brought to light knowledge gaps concerning British Muslim communities as well as Islamic and Muslim laws, specifically regarding family issues. Thus, the Ministry of Justice promptly commissioned a research project on these matters. Having had the privilege of being named amongst the researchers responsible for mentioned ministerial project, this paper intends to build upon the collected material and analysed data in order to shed light upon some key-findings concerning the BritishSharīʿah Councils.The proposed discussion also pays attention not only to the latest products of the academic discourse on faith-based justice, but also to the political debate on sharīʿah-related matters, addressing two recently launched enquiries and a pending Bill introduced in the Parliament.